Fluctuation Analysis in a Queue with (L,N)-Policy and Secondary Maintenance. Discrete Time Parameter Process - Alzahrani, M.S.; Dshalalow, J.H. (Электронное моделирование, 2011)
This paper generalizes numerous classes of queues with vacationing servers. In our model, a server not only leaves the system, but he services packets of jobs at a secondary facility up until the total number of single jobs exceeds a specific threshold. The strategy of server processes is represented for different state of queue.We use various techniques (including fluctuation analysis) to deliver explicit formulas for the queueing processwith discrete time parameters.We also utilize some game-theoretic principles (namely sequential games) to efficiently construct our model. Обобщены многочисленные классы очередей с простаивающими серверами. В предлагаемой модели сервер не просто выходит из системы, а обрабатывает пакеты задач в фоновом режиме до тех пор, пока общее число одиночных заданий не превысит определенный порог. Представлена стратегия работы сервера при различных состояниях очереди. Использованы различные методики получения явных формул (включая флуктуационный анализ) для процесса массового обслуживания с дискретным временем, а также некоторые подходы теории игр (последовательные игры) для эффективного конструирования модели. Узагальнено багатoчисельні класи черг серверів що простоюють. В запропонованій моделі сервер не просто виходить з системи, а обробляє пакети задач у фоновому режимі до тих пір, поки загальне число поодиноких завдань не перевищить означений поріг. Представлено стратегію роботи сервера в умовах різного стану черги. Використано різні методики отримання явних формул (включаючи флуктуаційний аналіз) для процесу масового обслуговування з дискретним часом, а також деякі підходи теорії гри (послідовні ігри) для ефективного конструювання моделі.